HUBUNGAN KONSUMSI FAST FOOD TERHADAP MENARCHE DINI PADA MAHASISWI DI STIKes MEDISTRA INDONESIA TAHUN 2018 - Siregar, Renince (STIKes Medistra Indonesia, 2020)
Background: In Indonesia the age of menarche varies from 10 to 16 years, where menarche occurs earlier in adolescents living in urban areas than in rural youth. The results of the Basic Health Research report 2010 found that 20.9% of girls in Indonesia have experienced menarche at the age of less than 12 years. Purpose: Knowing the existence of fast food consumption relationship with the incidence of early menarche student in Health University Medistra Indonesia 2018. Method: The type of this research is Cross-sectional. The population in this study were female under 21 years old who become female students at Health University Medistra Indonesia which amounted to 135 students. The sample selection technique in this research was using startified random sampling technique by making sampling frame from student's list DIII Midwifery Levels 1 and 2 are listed on the data of each class. The data collection tools are selective. Data were analyzed using Chi-Square test with 90% confidence level. Result: Chi-square analysis shows the value of statistical test using t test value p value 0.04, there is significant influence to fast food to early menarche. Conclusion: There is a fast food consumption relationship to early menarche where p value <niali α (0.04 <0.05).